Online or Offline: Perception of English Students Toward Learning Speaking During The Pandemic - Titien Fatmawaty Mohammad; Nita Marada; Nifat Nifat; Sri Rahmi Handayani Hatta; Fajrianti Fajrianti (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Covid-19 pandemic caused learning methods that were initially offline to become online. Therefore, this study aims to analyze students’ perceptions toward speaking during the pandemic. Quantitative descriptive method is used in this study with a questionnaire as an instrument. The results indicate that students respond positively toward online learning. This is evidenced by 54.81% of students who are inclined towards offline learning. While, the results based on gender, there are not specific difference between male and female students. Where 59.33% of male students give positive responses to online learning and 50.69% of female students gave positive responses to online learning.